2022
DOI: 10.1007/s10344-022-01602-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic traces of dispersal and admixture in red deer (Cervus elaphus) populations from the Carpathian Basin

Abstract: After the last glacial, the Carpathian Basin was repopulated from either eastward or northward colonisation routes for various species; one of these was the emblematic member of the European megafauna, the red deer, Cervus elaphus. We analysed 303 red deer individuals from the middle of the region, in seven Hungarian game reserves, at ten microsatellite loci (C01, C229, T26, T108, T123, T156, T172, T193, T501, T507), to investigate the genetic diversity of these subpopulations. We discovered high levels of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…For comparison, the DeerPlex markers in Hungarian red deer were all polymorphic (sample size=303). The marker with the lowest number of alleles had seven alleles (C229) and the marker with the highest number of alleles had 27 alleles (T156) (FRANK et al 2022). Other studies regarding fallow deer showed similar results, suggesting the potential causes to be the Pleistocene extinction, bottleneck effect, human-mediated reintroduction, and other anthropogenic effects (BAKER et al 2017).…”
Section: Resultsmentioning
confidence: 68%
“…For comparison, the DeerPlex markers in Hungarian red deer were all polymorphic (sample size=303). The marker with the lowest number of alleles had seven alleles (C229) and the marker with the highest number of alleles had 27 alleles (T156) (FRANK et al 2022). Other studies regarding fallow deer showed similar results, suggesting the potential causes to be the Pleistocene extinction, bottleneck effect, human-mediated reintroduction, and other anthropogenic effects (BAKER et al 2017).…”
Section: Resultsmentioning
confidence: 68%
“…Genetic structure analyses have been conducted in red deer populations across various European regions including the Iberian Peninsula [46][47][48][49], France [50,51], Luxemburg [52], Belgium [53], Scotland [20,54], Ireland [55], Germany [56,57], Denmark [58], Poland [59], Sweden [60], Norway [61], Czech Republic [62], Hungary [63], Croatia [64], Italy [65], or Greece [66]. Furthermore, assessments of genetic structure at a continental scale have also been carried out [67].…”
Section: Introductionmentioning
confidence: 99%